PEMBELAJARAN GEOGRAFI BERBASIS DIGITALISASI DALAM PENINGKATAN HASIL BELAJAR SISWA KELAS XI DI SMA NEGERI 4 KOTA BENGKULU - Fevi Wira Citra; deki saputra; Edwar Edwar; Nurmintan Silaban (Universitas Nusa Cendana, 2025)
This research aims to determine the differences in digitalization-based geography learning in improving the learning outcomes of class XI students at SMA Negeri 4 Bengkulu City. The method used in this research is Quasi experimental nonequivalent control group design. The population was 68 students from class XI IPS, the research samples were 2 classes. The sample for class XI IPS 1 as an experimental class uses a digitalization-based learning model and class XI IPS 2 as a control class uses conventional learning. Data collection techniques use pre-test and post-test. The analysis technique consists of validity test, reliability test, normality test, paired sample T-test test, and independent sample T-test test using the SPSS26 application. The average pre-test score in the experimental class was 61.17 and in the control class the average was 54.82, and the average post-test result in the experimental class was 78.70 and in the control class the average was 59.05. . Based on the results of the hypothesis test that has been carried out, it was found that the sig (2-tailed) value = 0.000 <0.05, so it can be concluded that Ho is rejected and Ha is accepted. From the research results, it can be concluded that learning using digitalization-based methods has differences in learning outcomes during the geography learning period towards improving student learning outcomes Keywords: Geography, Digitalization